miR-1229-3p as a Prognostic Predictor Facilitates Cell Viability, Migration, and Invasion of Hepatocellular Carcinoma - Zhang, Chunhong; Zhang, Qi; Li, Honghai; Wu, Yan (Hormone and Metabolic Research, 2021)
Hepatocellular carcinoma (HCC) remains one of the most prevalent human malignancies with high mortality. Increasing studies have revealed microRNAs (miRNAs) play crucial roles in the tumorigenesis and progression of cancers. The current study investigated the expression levels of miR-1229-3p and its potential role in HCC. This study enrolled 121 HCC patients. The expression of miR-1229-3p was measured using RT-qPCR in HCC tissue samples and cell lines. The association of miR-1229-3p expression with clinical parameters and patients’ prognosis was analyzed by χ2 test, Kaplan–Meier, and multivariate Cox regression analyses, respectively. The functions of miR-1229-3p in HCC cells were explored by CCK-8 assay, Transwell migration, and invasion assays. miR-1229-3p was upregulated in HCC tissue samples and cell lines. The upregulation of miR-1229-3p was related to positive lymph node metastasis and advanced TNM stages and predicted with patients’ poor prognosis. Overexpression of miR-1229-3p facilitated cell viability and metastasis of HCC cells while knockdown of miR-1229-3p suppressed cell viability and metastasis of HCC cells in vitro. miR-1229-3p may function as an oncogenic role in HCC via promoting cell viability and metastasis. Moreover, miR-1229-3p may be a predictive marker for tumor development and prognosis of HCC patients.
Keywords: hepatocellular carcinoma; miR-1229-3p; migration; invasion; viability